Comparison of extraperitoneal laparoscopic radical prostatectomy and open retropubic radical prostatectomy at Ramathibodi Hospital, Thailand: A retrospective review - Wisoot Kongcharoensombat (2018)
Objective: To compare perioperative outcomes of open radical retropubic prostatectomies (O-RRP) and extraperitoneal laparoscopic radical prostatectomies (E-LRP), focusing on operative time, blood loss, length of hospital stay, time to drain removal, and surgical margin status. Material and Method: The authors reviewed the medical histories of 173 patients treated for prostate cancer by radical prostatectomy at Ramathibodi Hospital between January 1997 and August 2010. Eighty-one patients were treated with O-RRP and 52 were treated with E-LRP. The remaining forty cases were omitted from the present study due to incomplete data (such as incomplete operative note, history) or if the patient had post transurethral prostatectomy or post androgen deprivation therapy. Open radical retropubic prostatectomies were performed by two experienced surgeons, and laparoscopic extraperitoneal radical prostatectomies were performed by a single surgeon. The following data were collected and compared between treatments, operative time, blood loss, length of hospital stay, time to drain removal, and surgical margin status. Results: Preoperative patient data indicated that both groups were comparable in age, height, prostate-specific antigen (PSA) levels, and Gleason scores from transurethral ultrasound guided biopsy. However, body weight and BMI was significantly higher in the O-RRP group. Estimated blood loss was significantly lower in the E-LRP group (median = 600 ml, range = 50-4,000 ml) than in the O-RRP group (median = 2,000 ml, range 200-7,500 ml) (p < 0.001). The length of hospital stay in the E-LRP group (median = 8 days, range = 4-27 days) was significantly shorter than in the open group (median = 11 days, range = 5-37 days) (p < 0.001). There were no significant differences between operative times, times to drain removal, or surgical margin statuses. Conclusion: The present study shows that patients who underwent E-LRP experienced less blood loss and shorter hospital stays than patients who underwent O-RRP.